How to Make a Bed Bug Interceptor Trap out of Common Household Items - Benjamin A. Hottel; Rebecca W. Baldwin; Roberto M. Pereira; Philip G. Koehler (EDIS)
Bed bugs have become an increasingly common pest problem throughout the United States. To discover whether bed bugs are present in a room or a piece of furniture, you can make interceptor traps out of commonly found household items and disposable plastic containers. This 4-page fact sheet was written by Benjamin A. Hottel, Rebecca W. Baldwin, Roberto M. Pereira, and Philip G. Koehler, and published by the UF Department of Entomology and Nematology, January 2014.